2018
DOI: 10.12737/textbook_5a93bd34dacb77.48838994
|View full text |Cite
|
Sign up to set email alerts
|

Investment analysis

Abstract: The basic provisions and the content of economic analysis in the process of investment activities of enterprises and organizations. The article reveals the concept and content of investment and investment activity, considers the main tools of economic calculations and justifications during the investment analysis, methods of analysis of the investment market, forms and methods for determining, calculating and analyzing the economic efficiency of investment projects, sources of financial support for investments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In the tutorial of professor Serov E.N. [8] it is indicated that if there are specific normative values for the joints compliance and an ar-bitrary level of their bearing capacity use, the deflection caused by the joints compliance definition, considering the forces acting in them, should be determined by the formula:…”
Section: Figure 1 -General View Of the Atrium And Nodal Jointmentioning
confidence: 99%
“…In the tutorial of professor Serov E.N. [8] it is indicated that if there are specific normative values for the joints compliance and an ar-bitrary level of their bearing capacity use, the deflection caused by the joints compliance definition, considering the forces acting in them, should be determined by the formula:…”
Section: Figure 1 -General View Of the Atrium And Nodal Jointmentioning
confidence: 99%